THE IMPORTANCE OF PERFECT HUMAN IDEAS IN THE VIEWS OF ALISHER NAVOI FOR THE PRESENT - Nurbayeva Marvarid Tavakalovna (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, Alisher Navoi touched upon the glorification of the idea of perfect man in his works and its importance for the present time. It was emphasized that the educational significance of Alisher Navoi’s works is high in the education of modern youth. The fan, who got acquainted with the article, realizes how important the works of Navoi are for the education of a perfect person.